ANALISIS DAN PERANCANGAN SISTEM INFORMASI CUSTOMER RELANTIONSHIP MANAGEMENT (CRM) UNTUK MENINGKATKAN PENJUALAN PADA TOKO OBAT PERTANIAN CV. MARINA AGRO KERINCI BERBASIS WEB - Hendriani, Sisi; Junita, Dewi; Uli, Desti Monika; Zurman; Adha, Afifah Cahayani (LPPM Universitas Awal Bros, 2023)
At CV. Marina Agro is buying and selling activities Still in manual form and not yet computerized. Customers come to the store sometimes the product is sold out. This can create a negative impression to quality service from CV. Marina Agro, as well as cases when buyers are busy, here because of a short age of personnel sometimes there are customers who are not served optimally. Therefore, an Information System was implemented Customer Relationship Management in order to help improve and maximize the quality of service and sales at CV. Marina Agro. By using System Information Customer Relationship Management can speed up and make it easier for customers to place orders without come directly to Shop. That way all the needs and desires of new and old customers will be fulfilled.